The Impact of Artificial Intelligence on Financial Management Efficiency : Narrative Literature Review - Safna Deviputri Suwandy (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This literature review examines the structural transformation of financial management driven by the integration of Artificial Intelligence (AI) and financial technology (fintech). Through a synthesis of recent scholarly findings, this study highlights that AI serves as a powerful catalyst for operational efficiency, significantly enhancing financial performance metrics such as Return on Assets (ROA) and Return on Equity (ROE) by optimizing cost structures and predictive decision-making processes. While these technologies facilitate broader financial inclusion by lowering entry barriers for unbanked populations, they also introduce systemic paradoxes, including algorithmic bias, data privacy concerns, and the challenges of